STUDY THE EFFECT OF ZIRCONIUM, NICKEL AND HEAT-TREATMENTS ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF COLD-ROLLED AA6111 ALLOY - Saba Jameel Hassan; Basem Al-Zubaidy; Saad Hameed Al-Shafaie (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The cold rolling effect on the microstructure and mechanical properties of recycled AA6111 alloy with Zr or/and Ni were investigated. All alloys were produced by the stir-casting method. homogenization heat treatment (500 ºC for 6 hours) was performed on AA6111 alloy only. The alloys were solutionized (at 540 ºC for 30 minute) and artificially aged (at 180 ºC for 10 hours). The optical micrograph, scanning-electron microscope (SEM) and X-ray Diffraction (XRD) studies for all samples. The microstructure analysis displayed different fine intermetallic phases distributed in large amounts in alloys containing Zr or/and nickel compared to AA6111 alloy. The combined alloying elements' addition effect with the cold rolling effect and artificial aging led to great improvements in the mechanical properties, where the hardness and tensile properties of all alloys increased. The AA6111+0.41wt%Ni alloy showed the highest hardness value, as it increased to 161 HV after artificial aging, while the AA6111+0.54wt%Zr alloy showed the highest YS and UTS, which increased to 252 MPa and 342 MPa, respectively.